The Impact of Psoriasis and Metabolic Syndrome on the Systemic Inflammation and Oxidative Damage to Nucleic Acids - Drahomira Holmannova; Lenka Borska; Ctirad Andrys; Pavel Borsky; Jan Kremlacek; Kvetoslava Hamakova; Vit Rehacek; Andrea Malkova; Tereza Svadlakova; Vladimir Palicka; Jan Krejsek; Zdenek Fiala (Journal of Immunology Research)
Background. Psoriasis is a chronic systemic inflammatory disease associated with a wide range of comorbidities, including metabolic syndrome (MetS). Serum calprotectin, ANGPTL8, and oxidative damage to nucleic acids might be associated with both diseases. The presented study describes the influence of psoriasis and MetS on the serum levels of markers of systemic inflammation (calprotectin and ANGPTL8) and markers of oxidative damage to nucleic acids. The applicability of serum levels of calprotectin and ANGPTL8 for monitoring of the activity of psoriasis (diagnostic markers) is also evaluated. Methods. Clinical examination (PASI score, MetS), enzyme-linked immunosorbent assay (ELISA), and Enzyme Immunoassay (EIA). Serum calprotectin, ANGPTL8, 8-hydroxy-2′-deoxyguanosine, 8-hydroxyguanosine, and 8-hydroxyguanine. Results and Conclusions. The psoriasis significantly increased the serum level of calprotectin and the serum level of oxidative damage to nucleic acids, however not the serum level of ANGPTL8. The presence of MetS did not significantly affect the serum levels of calprotectin, ANGPTL8, and oxidative damage to nucleic acids in either psoriasis patients or controls. It seems that the serum level of calprotectin (but not the serum level of ANGPTL8) could be used as a biomarker for monitoring the activity of psoriasis.